2011
DOI: 10.1002/lt.22247
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of lung, head and neck, esophageal, and kidney and urinary tract carcinomas after liver transplantation: The effect of smoking withdrawal

Abstract: Liver transplant recipients have an increased risk of malignancy. Smoking is related to some of the most frequent causes of posttransplant malignancy. The incidence and risk factors for the development of neoplasia related to smoking (head and neck, lung, esophageal, and kidney and urinary tract carcinomas) were studied in 339 liver transplant recipients. Risk factors for the development of smoking-related neoplasia were also studied in 135 patients who had a history of smoking so that it could be determined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 25 publications
(48 reference statements)
3
79
0
Order By: Relevance
“…12 Some studies have shown beneficial effects of smoking cessation on liver and kidney recipients. 13,14 However, there are insufficient data about smoking-related morbidity and mortality in liver donors.…”
Section: Discussionmentioning
confidence: 99%
“…12 Some studies have shown beneficial effects of smoking cessation on liver and kidney recipients. 13,14 However, there are insufficient data about smoking-related morbidity and mortality in liver donors.…”
Section: Discussionmentioning
confidence: 99%
“…Active smoking after transplantation in ALD has been shown to be an independent predictor of long-term morbidity and mortality, either from cardiovascular complications or from de novo neoplasms. 61 Herrero et al 62 showed that withdrawal smoking was associated with lower risk of de novo malignancies after liver transplantation. Also, smoking is a major risk for cardiovascular disease, and thus contributes to late mortality after transplantation, independent of malignancy development.…”
Section: Risk Of Malignancy After Liver Transplantmentioning
confidence: 99%
“…Tumors in the head and neck area cover about 3.5-15% of all malignancies after transplantation [3][4][5]. A large part of these head and neck cancers (HNC) are squamous cell carcinomas (SCC) of the lip or oropharynx [6][7][8][9][10][11][12]. The exact mechanism for carcinogenesis under immunosuppression remains unclear, however it is clearly a multifactorial process [2].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of tobacco exposure and the synergistic carcinogenic effect of alcohol have long been demonstrated in the general population. In transplant patients, tobacco and/or alcohol also increase the risk of developing HNC (HR = 9.2; 95% CI 2.0-42.0; p = 0.004) [4,6,8,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation